1997
DOI: 10.1161/01.hyp.30.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Determinants of Sodium Retention in Mild Heart Failure

Abstract: The onset and the mechanisms leading to Na+ retention in incipient congestive heart failure (CHF) have not been systematically investigated. To investigate renal Na+ handling in the early or mild stages of CHF, Na+ balance and renal clearances were assessed in 10 asymptomatic patients with idiopathic or ischemic dilated cardiomyopathy and mild heart failure (HF) off treatment (left ventricular ejection fraction, 29.7+/-2%) and in 10 matched normal subjects during a diet containing 100 mmol/d of NaCl and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Natriuretic peptide levels were affected inconsistently among studies; levels did not change significantly with dietary sodium modification in 4 studies using very low to moderate dietary sodium restriction, 34,36 -38 decreased in 2 studies with a moderate-to-high sodium diet, 35,39 and increased in 3 studies with a low-sodium diet. 40 -42 Levels of neurohormones, such as PRA, norepinephrine, angiotensin-II, and urinary aldosterone, increased with dietary sodium restriction regardless of degree of restriction.…”
Section: Physiological and Neurohormonal Responsesmentioning
confidence: 97%
See 2 more Smart Citations
“…Natriuretic peptide levels were affected inconsistently among studies; levels did not change significantly with dietary sodium modification in 4 studies using very low to moderate dietary sodium restriction, 34,36 -38 decreased in 2 studies with a moderate-to-high sodium diet, 35,39 and increased in 3 studies with a low-sodium diet. 40 -42 Levels of neurohormones, such as PRA, norepinephrine, angiotensin-II, and urinary aldosterone, increased with dietary sodium restriction regardless of degree of restriction.…”
Section: Physiological and Neurohormonal Responsesmentioning
confidence: 97%
“…Two studies by Volpe and colleagues 35,36 concluded that moderate-to-high sodium intake had no hemodynamic effects on NYHA I to II patients Only consensus opinion of experts, case studies, or standard of care; FairϭBenefits exceed the harms but quality of evidence is not as strong; 1ϩ ϭ well-conducted meta-analysis, systemic reviews, or randomized controlled trials with low risk of bias. NYHA indicates New York Heart Association.…”
Section: Physiological and Neurohormonal Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium loading increases renal plasma flow (RPF) and GFR in mild heart failure patients [6]. GFR is determined mainly by filtration pressure and filtration coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…Volpe et al (9) described the effects of increased sodium intake on GFR, renal plasma fl ow and renal vascular resistance in mild asymptomatic HF. In both normal and mild heart failure subjects, the increased sodium intake (250 mmol/day vs. 100 mmol/day) caused GFR and renal plasma fl ow and fi ltered load of sodium to increase signifi cantly and renal vascular resistance to drop but, while the fractional clearance of water, excretion of potassium and sodium increased in normal subjects, it was signifi cantly reduced in the mild CHF group.…”
Section: Deranged Sodium Handlingmentioning
confidence: 99%